Masala mix pounded by machines - Mumbai Archive Project Team (Jio Institute, 2024)
In the past, in East Indian neighbourhoods like Vasai (Bassein), it was common to find groups of women (called masalewalis) going from house to house to do the roasting and grounding. Manual pounding was a labour-intensive process spread over two or three days. Over the years, the pounding process has become entirely mechanised. Families now send the masala mix to mills, where it is pounded by machines.